(untitled) (Palimpsesto, 2017)
By analyzing the Condor Operation trial held in Italy, this article seeks to point out the limits of the criminal approach, especially when conducts from abroad, to answer to the institutional violence carried out through the transnational clandestine repressive cooperation which defined this operation. In order to do so, this work goes through the case’s genesis starting by the context of the initial criminal lawsuit in 1999 and traces its evolution until the formal opening of the trial in court. It then analyzes the trial in itself up to the court’s verdict by drawing on interviews of various actors (complainants, survivor witnesses and expert witnesses) and on records of the public hearings. Finally, some unresolved questions will be pointed out regarding the verdict and its motives pertaining to the repressive coordination.